Nanocompósitos cerâmicos a partir do processo de moagem mecânica de alta energia - Carreño, Neftalí L. V.; Garcia, Irene T. S.; Santos, Luís P. S.; Fabbro, Maria T.; Keyson, Dawy; Leite, Edson R.; Longo, Elson [UNESP]; Fajardo, Humberto V.; Probst, Luiz F. D. (Sociedade Brasileira de Química, 2008)
Pb/Ti, Sn and Mg-based nanocomposite materials were prepared by the high-energy mechanical milling of commercial powders. The surface of these ceramic compounds was strongly influenced by the doping, diameter of the milling spheres and time of the mechanical milling (amorphization process). Such milling leads to the formation of nanocrystalline materials. The mechanical processing parameters of these compounds were investigated through Brunauer, Emmett and Teller isotherms, wide angle X-ray diffraction, transmission electron microscopy and CO2 adsorption.
Ceramic nanocomposites from the hight-energy mechanical milling process
Keywords: nanocomposite; high-energy attrition mill; rare earth